Academic Roles of Educational Leaders for Quality Learning Environment in the public and private Universities at Lahore - Nizami, Rahila; Rashid, Khalid (Annals of King Edward Medical University, 2018)
Background: Quality learning environments are innovative, transformative and collaborative thus facilitating the educational processes. This study was designed to figure out the academic roles of higher educational leaders for quality learning environment in the public and private universities at Lahore. The objective was to identify the gaps in the academic roles being played and entrusted to the educational leaders. Methodology: A cross-sectional study was conducted at Lahore, among the public and private sector universities. Stratified sampling technique was opted and universities having the faculties of natural sciences, arts & humanities, management sciences and social sciences were selected for study population. The educational leadership of the universities was categorized into senior and junior faculty and all the faculty members of sampled universities were invited for participation. The data was collected through the self-designed, validated and pilot tested five-point rating scale. The collected data was entered into the statistical package for social sciences. Chi square test was used to determine the association using p value --- 0.05 as significant. Results: Findings of the research revealed that there was a significant difference between the academic roles among the faculty of public and private universities. Conclusions: The study concludes that higher educational leaders must identify and practice their roles to enhance the quality of the learning environment of universities.